Evolution of Vertebrate Tissues Driven by Differential Modes of Gene Duplication. - MC LYSAGHT, AOIFE (My University, 2012)
In this study, we investigated the evolution of vertebrate tissues by examining the potential association among gene expression, duplication, and base substitution patterns. In particular, we compared whole-genome duplication (WGD) with small-scale duplication (SSD), as well as tissue restricted with ubiquitously expressed genes. All patterns were also analysed in the light of gene evolutionary rates. Among those genes characterized by rapid evolution and expressed in a restricted range of tissues, SSD was represented in a larger proportion than WGD. Conversely, genes with ubiquitous expression were associated with slower evolutionary rates and a larger proportion of WGD. The results also show that evolutionary rates were faster in genes expressed in endodermal tissues and slower in ectodermal genes. Accordingly, the proportion of the SSD and WGD genes was highest in the endoderm and ectoderm, respectively. Therefore, quickly evolving SSD genes might have contributed to the faster evolution of endodermal tissues, whereas the comparatively slowly evolving WGD genes might have functioned to maintain the basic characteristics of ectodermal tissues. Mesenchymal tissues occupied an intermediate position in this regard, whereas the patterns observed for haemocytes were unique. Rapid tissue evolution could be related to a specific gene duplication mode (SSD) and faster molecular evolution in response to exposure to the external environment. These findings reveal general patterns underlying the evolution of tissues and their corresponding genes. ? The Author 2012.
PUBLISHED
Keywords: gene duplication; ohnologue; gene expression; tissue evolution; gene duplication; ohnologue; gene expression; tissue evolution